Long-range comparison of human and mouse Sprr loci to identify conserved noncoding sequences involved in coordinate regulation - Martin, Natalia; Patel, Satyakam; Segre, Julia A. (Genome Research, 2004)
Mammalian epidermis provides a permeability barrier between an organism and its environment. Under homeostatic conditions, epidermal cells produce structural proteins, which are cross-linked in an orderly fashion to form a cornified envelope (CE). However, under genetic or environmental stress, specific genes are induced to rapidly build a temporary barrier. Small proline-rich (SPRR) proteins are the primary constituents of the CE. Under stress the entire family of 14 Sprr genes is upregulated. The Sprr genes are clustered within the larger epidermal differentiation complex on mouse chromosome 3, human chromosome 1q21. The clustering of the Sprr genes and their upregulation under stress suggest that these genes may be coordinately regulated. To identify enhancer elements that regulate this stress response activation of the Sprr locus, we utilized bioinformatic tools and classical biochemical dissection. Long-range comparative sequence analysis identified conserved noncoding sequences (CNSs). Clusters of epidermal-specific DNaseI-hypersensitive sites (HSs) mapped to specific CNSs. Increased prevalence of these HSs in barrier-deficient epidermis provides in vivo evidence of the regulation of the Sprr locus by these conserved sequences. Individual components of these HSs were cloned, and one was shown to have strong enhancer activity specific to conditions when the Sprr genes are coordinately upregulated.